Early commensal interaction between humans and hares in Neolithic northern China. (June 2020) - Sheng, Pengfei; Hu, Yaowu; Sun, Zhouyong; Yang, Liping; Hu, Songmei; Fuller, Benjamin T.; Shang, Xue
Abstract: Abstract : Human influence on ecological niches can drive rapid changes in the diet, behaviour and evolutionary trajectories of small mammals. Archaeological evidence from the Late Neolithic Loess Plateau of northern China suggests that the expansion of millet cultivation created new selective pressures, attracting small mammals to fields and settlements. Here, the authors present direct evidence for commensal behaviour in desert hares ( Lepus capensis ), dating to c . 4900 years ago. Stable isotope ratio analysis of hare bones from the Neolithic site at Yangjiesha shows a diachronic increase in a C4 (millet-based) diet, revealing, for the first time, the expansion of ancient human-hare interactions beyond the predator-prey relationship.